Ռումինիայի հայկական համայնքների քաղաքական գործունեությունը (15 – 21-րդ դդ.) - Արսեն Արզումանյան (ՀՀ ԳԱԱ հրատ.)
В статье политическая активность армянских общин в румынских княжествах, а также в объединенной Румынии изучена сквозь призму нескольких аспектов - приобретение автономии армянскими общинами в разных городах,деятельность армянских политических лиц и т.д. Статья также рассматривает участие армянской общины в сегодняшней политической жизни Румынии в лице Союза армян Румынии. В статье использованы материалы из научной литературы, а также информация, собранная во время личных встреч автора с представителями армянской общины.This article examines the political activity of the Armenian communities of Romania through various aspects: the realization of autonomy in certain Romanian towns by the Armenian communities; the activity of numerous Armenian political leaders, etc. The article also encompasses Armenian community’s (Union Of Armenians of Romanian) involvement in today’s political life of Romania.In this paper use is made of scientific articles of different publications,various information gathered by Arsen Arzumanyan’s personal contacts with the members of the Armenian community as well.
Keywords: Armenian Diaspora; Political Science; Political science